Possible connection between intestinal tuft cells, ILC2s and obesity - Yang, Hong; Huang, Yu-Xing; Xiong, Pei-Yu; Li, Jin-Qian; Chen, Ji-Lan; Liu, Xia; Gong, Yan-Ju; Ding, Wei-Jun (Frontiers in Immunology, 2024)
Intestinal tuft cells (TCs) are defined as chemosensory cells that can "taste" danger and induce immune responses. They play a critical role in gastrointestinal parasite invasion, inflammatory bowel diseases and high-fat diet-induced obesity. Intestinal IL-25, the unique product of TCs, is a key activator of type 2 immunity, especially to promote group 2 innate lymphoid cells (ILC2s) to secret IL-13. Then the IL-13 mainly promotes intestinal stem cell (ISCs) proliferation into TCs and goblet cells. This pathway formulates the circuit in the intestine. This paper focuses on the potential role of the intestinal TC, ILC2 and their circuit in obesity-induced intestinal damage, and discussion on further study and the potential therapeutic target in obesity.